Pygmalion Karya Bernard Shaw dalam Edisi 1957 dan 2000 - M. Yuseano Kardiansyah (Balai Bahasa Provinsi Riau, 2019)
This research contains a comparative study on two printed drama scripts of Bernard Shaw’s “Pygmalion”. Here, the discussion covers a study toward two scripts published in 1957 and 2000, in the perspective of philology that demonstrates both textology and codicology. The objective of this research is to reveal the variation of Pygmalion printed scripts published in those two different years, 1957 and 2000. Eventually, through the analysis conducted to those two scripts, it is found that there are similarity and distinction, in which the distinction is in a form of variations between them, that also leads to the background of why such a variation could possibly be emerged.